Retrospective analysis of patients with depression assisted in a specialized mental health service (Research, Society and Development, 2021)
Objective: to describe the application of retrospective analysis to patients with depression assisted in a specialized mental health service in light of nursing care. Methodology: Descriptive research with a qualitative and retrospective approach, developed in a service of the psychosocial care network in a city in the interior of Ceará, in the period from April to May 2019, through interviews and survey of the patient's history. Results: It was observed that traumas related to the patient's personal and family history are present in speech and have repercussions on daily life activities and worsening of the clinical picture. The presence of auditory hallucinations and suicidal thoughts revealed the need for specific care. The listed diagnoses were: Chronic confusion; Impaired social interaction; Disposition for improved family processes; Post-trauma syndrome; Fear; Disposition for improved spiritual well-being; Risk of Suicide. Conclusion: It is emphasized that the effectiveness of multiprofessional care is related to the retrospective approach of the patient and the care of the individual in a biopsychosocial way, especially in the light of nursing care.